Jatropha press cake as organic fertilizer in lettuce cultivation - José R. Mantovani; Jéssica da S. Bernardes; Paulo R. C. Landgraf (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In biodiesel production, vegetable press cake is obtained as waste, and a suitable destination for jatropha press cake would be the use in agriculture as organic fertilizer. This study aimed to evaluate the effect of jatropha press cake on soil fertility attributes and on lettuce production and accumulation of nutrients in the shoots. The experiment was conducted in pots in a greenhouse, in a randomized block design with eight treatments and five replicates. The treatments consisted of doses of jatropha press cake equivalent to 0, 0.5, 1.0, 2.0, 4.0, 8.0, 16.0 and 32.0 t ha-1. Portions of 5.5 dm3 of soil received limestone, phosphate fertilizer and the doses of jatropha press cake, and remained incubated for 30 days. After incubation, soil samples were collected, each pot received one lettuce seedling and the experiment was carried out for 45 days. The organic fertilization with jatropha press cake increased the contents of nutrients in the soil, especially K+, but caused increment in soil acidity and electrical conductivity. The use of jatropha press cake as organic fertilizer decreased lettuce production and accumulation of nutrients in the shoots.